A test of torque-control and equilibrium-point models of motor control - Gottlieb, Gerald L. (Human movement science, 2000)
Based upon predictions of equilibrium-point (EP) models of motor control, a recent article by Jaric et al. (1999) [ Human Movement Sciences, 18, 49–66] reported that the peak velocity (PV) of an inertially loaded single degree-of-freedom elbow movement was not altered to a statistically distinguishable degree by the accuracy of the subject's expectation about the size of the load. They concluded that their results confirmed their EP models and were incompatible with what they described as torque-control models. A review of the literature and analysis of a more extensive set of data does not support that conclusion. To the contrary, if the actual load is heavier (or lighter) than expected, it is moved more slowly (or faster) than it would have been, had expectation matched reality. Torque-control models predict those consequences, EP models do not.